Rapid Detection of Hepatitis B Virus in Blood Samples Using a Combination of Polymerase Spiral Reaction With Nanoparticles Lateral-Flow Biosensor - Lin, Lin; Guo, Jinshuai; Liu, Haiyang; Jiang, Xiaofeng (Frontiers in Molecular Biosciences, 2021)
A rapid, highly sensitive, and robust diagnostic technique for point-of-care (PoC) testing can be developed using the combination of the nanoparticle-based lateral flow biosensors (LFB) and isothermal nucleic acid amplification technology. Here, we developed a polymerase spiral reaction (PSR) containing FITC-labeled DNA probes coupled with the nanoparticle-based LFB assay (PSR-LFB) to detect the amplified products to detect HBV visually. Under the optimized conditions, the PSR assay involved incubation of the reaction mixture for 20 min at 63°C, followed by visual detection of positive amplicons using LFB, which would generate a red test line based on the biotin/streptavidin interaction and immunoreactions, within 5 min. A cross-reactivity test revealed that the developed PSR-LFB assay showed good specificity for HBV and could distinguish HBV from other pathogenic microorganisms. For the analytical sensitivity, the limit of detection (LoD) of PSR-LFB assay was recorded as 5.4 copies/mL of HBV genomic DNA, which was ten-times more sensitive than qPCR and loop-mediated isothermal amplification (LAMP). Additionally, all the HBV-positive (29/82) samples, identified using ELISA, were also successfully detected by the PSR-LFB assay. We found that the true positive rate of the PSR-LFB assay was higher than that of qPCR (100 vs. 89.66%, respectively), as well as the LAMP assay (100 vs. 96.55%, respectively). Furthermore, the integrated procedure could be completed in 60 min, including the processing of the blood samples (30 min), an isothermal reaction (20 min), and result visualization (5 min). Thus, this PSR-LFB assay could be a potentially useful technique for PoC diagnosis of HBV in resource-limited countries.